Monthly and Annual Rainfall Variability in Peninsular Malaysia - Camerlengo, Alejandro Livio; Somchit, Nhakhorn (Universiti Putra Malaysia Press, 2000)
This paper re-addresses the study of the rainfall variability in Peninsular Malaysia. An earlier investigation has been conducted forty years ago. Due to the fact that: (1) a larger and more sophisticated number of meteorological stations is nowadays in place, and (2) the effect that global warming has on precipitation, we feel that a new study of rainfall variability is both timely and pertinent. This is, therefore, the aim of this particular study. Our results show that larger variability does not (always) occur whenever lowest rainfall is recorded.